MODEL EROSI DAN SEDIMENTASI MELALUI ANALISIS SOIL AND WATER ASSESMENT TOOL (SWAT): STUDI KASUS SUB-DAS CIKAO, KABUPATEN PURWAKARTA, PROVINSI JAWA BARAT - Ramdhan, Farda; Iskandar, Teuku Yan Waliana Muda; Listiawan, Yudhi (Fakultas Teknik Geologi Universitas Padjadjaran, 2023)
This research was conducted in the Cikao sub-watershed, which is in Purwakarta Regency, West Java Province. Cikao Sub-Watershed is a part of the Citarum Watershed, which contributes the highest erosivity to Citarum Watershed. This is reinforced by the activity of sedimentation excavation in Cikao river area. This research was conducted to determine the erosion and sedimentation potential rate in Cikao Sub-Watershed using Soil and Water Assessment Tool (SWAT) which can be considered for watershed management plan. This SWAT model is quantitative analysis using climate, hydrology, land use, soil type, and slope data. The results show that erosion rates in the Cikao Sub-Watershed are 845.7 tons/ha/year and sedimentation rates are 653.62 tons/ha/year. The erosion levels in the Cikao Sub-Watershed consist of very slight class 2041.99 ha, slight class 1956.03 ha, and moderate class is 3027.32 ha. And the sedimentation levels consist of a very low class 3004.02 ha, a low class 134.78 ha, a moderate class 131.62 ha, and a very high class 3754.92 ha.Keywords: SWAT, Cikao Sub-Watershed, Erosion, Sedimentation